DIMENSI KEBIJAKAN STRATEGIS TRANSFORMATIF PENDIDIKAN MADRASAH DAN PERGURUAN TINGGI ISLAM - M. Yusuf Aminuddin (Ta‘lim)
This research aims to analyze the dimensions of transformative strategic policies in Islamic madrasah and higher education education, focusing on policies issued by the Ministry of Indonesia Religion . In the context of rapid social change and modernization, Islamic education faces complex challenges that require responsive and inclusive policies. Through a descriptive qualitative approach based on phenomenological studies, this research explores the experiences and perspectives of stakeholders in implementing education policies. The research results show that education policies must respond to diverse communities' needs, integrate local values, and create synergy between formal and non-formal education. In addition, improving the quality of human resources, active participation from the community, and innovation in the curriculum are the keys to achieving effective educational transformation. This research also emphasizes the importance of evaluation and monitoring in education policy to ensure sustainability and equal access to education. In this way, it is hoped that the resulting policies can contribute to the development of education that is not only academically competent but also forms strong character and moral values ​​in the younger generation so that they can contribute positively to community development